Correlation and path analysis in Indian mustard (Brassica juncea L) for morpho-physiological traits in early maturing genotypes - Ajay Pal Yadav,; Bhagirath Ram,; Hariom Kumar Sharma,; Bhupendra Singh Yadav,; Mahipal Yadav, (Journal of Oilseed Brassica, 2026)
Thirty advanced progenies along with three check varieties of Indian mustard (Brassica juncea) were evaluated duringRabi 2019-20. The analysis of variance showed significant difference among genotype for all the characters. Highestimate of heritability coupled genetic advance as percentage of mean was observed for 1000-seed weight, siliqua perplant and seed yield per plant. Medium heritability with medium genetic advance as percentage of mean was observedfor water retention capacity of leaves, membrane stability index and secondary branches per plant. Correlation coefficientreflected that seed yield per plant showed positive and significant association with primary branches per plant (0.83),excised-leaf water loss (0.52), secondary branches per plant (0.52), siliqua per plant (0.44), days to 50 % flowering (0.35),main shoot length (0.32) and plant height (0.24). Path coefficient at genotypic level studied that secondary branches perplant (0.28), water retention capacity of leaves (0.21), main shoot length (0.19), excised-leaf water loss (0.15), days tomaturity (0.09), primary branches per plant (0.08), siliqua per plant (0.07) had positive direct effect on seed yield per plantwas observed. Thus, morphological and physiological characters confer the potentiality of particular genotype andassociation with yield is suitable for genotype selection.